Molecular reorientation based diffraction in dihydropyridin doped nematic liquid crystal film - San, SE; Köysal, O; Okutan, M (Elsevier Sci Ltd, 2004)
The change of refractive index, originated by photo induced molecular reorientation, brings about a significant diffraction capability in a liquid crystal system doped by 1,4-dihydropyridin. Results of a grating diffraction experiment are reported for the constructed sample. The accessible diffraction efficiency is roughly of the order of 10% under the optimum conditions and analyzed results propose this novel system to be appropriate and promising for the excitation wavelength of an He-Cd laser. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: nematic liquid crystals; dye doped; dihydropyridin; molecular reorientation; grating diffraction